2004
DOI: 10.1128/jvi.78.1.329-339.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interaction between P143 and LEF-3 from Two Different Baculovirus Species: Choristoneura fumiferana Nucleopolyhedrovirus LEF-3 Can Complement Autographa californica Nucleopolyhedrovirus LEF-3 in Supporting DNA Replication

Abstract: The baculovirus protein P143 is essential for viral DNA replication in vivo, likely as a DNA helicase. We have demonstrated that another viral protein, LEF-3, first described as a single-stranded DNA binding protein, is required for transporting P143 into the nuclei of insect cells. Both of these proteins, along with several other early viral proteins, are also essential for DNA replication in transient assays. We now describe the identification, nucleotide sequences, and transcription patterns of the Choristo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
(43 reference statements)
2
13
0
Order By: Relevance
“…In addition, this construct could substitute for authenticate P143 in supporting DNA replication in transient assays but only in the presence of intact LEF-3. These results confirm previous experiments where fusing GFP to the CfMNPV P143 protein did not inhibit the ability of P143 to support DNA replication (2). From these results, we conclude that the presence of P143 in the nucleus is not sufficient to support DNA replication, in the absence of LEF-3.…”
Section: Vol 79 2005supporting
confidence: 81%
See 3 more Smart Citations
“…In addition, this construct could substitute for authenticate P143 in supporting DNA replication in transient assays but only in the presence of intact LEF-3. These results confirm previous experiments where fusing GFP to the CfMNPV P143 protein did not inhibit the ability of P143 to support DNA replication (2). From these results, we conclude that the presence of P143 in the nucleus is not sufficient to support DNA replication, in the absence of LEF-3.…”
Section: Vol 79 2005supporting
confidence: 81%
“…Three closely related species (AcMNPV, Rachiplusia ou MNPV [RoMNPV], and Bombyx mori NPV [BmNPV]) appear to have an insert in this region consisting of nine amino acids (eight are identical in all these viruses), including flanking basic amino acids and a proline, compared with other group I NPVs. We have previously shown that Christoneura fumifurana MNPV (CfMNPV) LEF-3 self-localizes to the nucleus of infected cells (2), suggesting that this nine-amino-acid region is not essential for nuclear localization. Since all of our constructs in the vector pHSEH are His tagged, there is a string of eight basic amino acids fused immediately upstream of any sequences cloned into this vector.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sf21 cells were transfected with 1 g of purified bacmid DNA as previously described (6). At various times after transfection, supernatants were harvested and titers were determined in 50% tissue culture infective dose (TCID 50 ) endpoint dilution assays (25) to determine the replication properties of BV produced by the various bacmids.…”
Section: Methodsmentioning
confidence: 99%